2018
DOI: 10.1007/s00018-018-2971-0
|View full text |Cite
|
Sign up to set email alerts
|

H19X-encoded miR-424(322)/-503 cluster: emerging roles in cell differentiation, proliferation, plasticity and metabolism

Abstract: miR-424(322)/-503 are mammal-specific members of the extended miR-15/107 microRNA family. They form a co-expression network with the imprinted lncRNA H19 in tetrapods. miR-424(322)/-503 regulate fundamental cellular processes including cell cycle, epithelial-to-mesenchymal transition, hypoxia and other stress response. They control tissue differentiation (cardiomyocyte, skeletal muscle, monocyte) and remodeling (mammary gland involution), and paradoxically participate in tumor initiation and progression. Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 153 publications
(151 reference statements)
6
42
0
Order By: Relevance
“…This miRNA cluster includes six miRNAs (miR‐424, miR‐503, miR‐542, miR‐450a‐1, miR‐450a‐2, and miR‐450b) and has postulated roles in cell differentiation, proliferation, plasticity, and metabolism, extensively reviewed by Wang et al . . In accordance to our data, members of this miRNA cluster were previously found to be increased in the skeletal muscle of patients with other muscle wasting diseases: in patients with amyotrophic lateral sclerosis, the expression levels of miR‐425, miR‐450b, miR‐503, and miR‐542 were increased .…”
Section: Discussionsupporting
confidence: 92%
“…This miRNA cluster includes six miRNAs (miR‐424, miR‐503, miR‐542, miR‐450a‐1, miR‐450a‐2, and miR‐450b) and has postulated roles in cell differentiation, proliferation, plasticity, and metabolism, extensively reviewed by Wang et al . . In accordance to our data, members of this miRNA cluster were previously found to be increased in the skeletal muscle of patients with other muscle wasting diseases: in patients with amyotrophic lateral sclerosis, the expression levels of miR‐425, miR‐450b, miR‐503, and miR‐542 were increased .…”
Section: Discussionsupporting
confidence: 92%
“…Such unusual genomic arrangements of the miRNAs intensively raise our attention to explore their possible regulatory functions. For example, the MIR1306 gene overlaps the DGCR8 coding region and the MIR675 gene is embedded in the first exon of H19 lncRNA, both of which are conserved in primates ( Morin et al, 2008 ; Friedländer et al, 2008 ; Keniry et al, 2012 ; Wang et al, 2018 ). It has been reported that the mir-1306 hairpin is cleaved by the Drosha-DGCR8 complex, which plays an important negative-feedback role in controlling DGCR8 expression ( Morin et al, 2008 ; Friedländer et al, 2008 ; Keniry et al, 2012 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MIR1306 gene overlaps the DGCR8 coding region and the MIR675 gene is embedded in the first exon of H19 lncRNA, both of which are conserved in primates ( Morin et al, 2008 ; Friedländer et al, 2008 ; Keniry et al, 2012 ; Wang et al, 2018 ). It has been reported that the mir-1306 hairpin is cleaved by the Drosha-DGCR8 complex, which plays an important negative-feedback role in controlling DGCR8 expression ( Morin et al, 2008 ; Friedländer et al, 2008 ; Keniry et al, 2012 ; Wang et al, 2018 ). H19 is an important imprinted gene involved in placental development prior to birth, which limits the growth of the placenta by regulating miR-675 processes ( Keniry et al, 2012 ; Wang et al, 2018 ; Han et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNA (lncRNA) is a member of the RNA family, with length of more than 200 nucleotides. In recent years, numerous studies have approved lncRNA involved in biological processes including proliferation, differentiation and apoptosis [13][14][15]. X-inactive specific transcript (XIST) is a dramatic example of lncRNA, which plays a key role in silencing of X-chromosome [16].…”
Section: Introductionmentioning
confidence: 99%